Alcalde Juan Carlos Del Águila Cardenas - Centro de Estudios Teológicos de la Amazonía (CETA) (My University, 2003)
SPANISH: Juramentación del Alcalde Provincial de Maynas Juan Carlos Del Águila Cárdenas. (2003-2006)
ENGLISH: Inauguration of the Provincial Mayor of Maynas Juan Carlos Del Águila Cárdenas (2003-2006).

SPANISH: Juramentación del Alcalde Provincial de Maynas Juan Carlos Del Águila Cárdenas. (2003-2006)
ENGLISH: Inauguration of the Provincial Mayor of Maynas Juan Carlos Del Águila Cárdenas (2003-2006).
Mayor Juan Carlos Del Águila Cárdenas
Keywords: S/N